THE TEN BEST PRACTICES FOR STUDENT MENTORING PROGRAM IN HIGHER EDUCATION: PROMISE AND PARADOX - Fazreena Mansor; Nur Fakhzan Marwan; Zaidatul Nadiah Abu Yazid; Mohd Samsuri Ghazali (Journal of Islamic, Social, Economics and Development, 2023)
Mentoring programs serve as a vital role in higher education offering students access to advice, encouragement, and growth experiences. This study outlines a comprehensive strategy for designing and implementing a successful mentoring program within the context of higher education. A total of five expert were recruited from the Universiti Teknologi MARA, Raub Campus to participate in our Nominal Group Technique (NGT) meetings. Data were collected and analyzed descriptively, and weighted according to ranking (1-3, lowest to highest priority) of domain. Experts’ rationales for the choices were analyzed thematically. The domain of ‘clear goals and objectives’, ‘training for mentors’, ‘peer groups activities’, and ‘feedback mechanism’ was recommended as the preferred measure of time period over which the domains were rated. The adoption of these recommendations will help standardize approaches to improving the mentoring program particularly in higher education in Malaysia.